VEHICLE THEFT CONTROL AND ACCIDENT LOCATION INTIMATION THROUGH SMS - Dr.A.RANGANAYAKULU , Mr.A.PRASAD , YAMANURI VYSHNAVI, NAGELLA SHEBA PALLAVI, BONDILI VARSHIKA BAI, BORRA VEDAKSHI, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Human life is more valuable than anything else, timely help is more important than lending a helpinghand. There are two main modules discussed in the project. The first module is password based securitysystem to access the vehicle and the second one is accident location intimation through SMS by usingGSM module.